2019
DOI: 10.1186/s13578-019-0357-0
|View full text |Cite
|
Sign up to set email alerts
|

CRISPRa-mediated FOXP3 gene upregulation in mammalian cells

Abstract: BackgroundForkhead box P3+ (FOXP3+) regulatory T cells (Tregs) are a subset of lymphocytes, critical for the maintenance of immune homeostasis. Loss-of-function mutations of the FOXP3 gene in animal models and humans results in loss of differentiation potential into Treg cells and are responsible for several immune-mediated inflammatory diseases. Strategies of increasing FOXP3 expression represent a potential approach to increase the pool of Tregs within the lymphocyte population and may be employed in therapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…CNS3 located at FOXP3 intron 1 (i.e., between exon 1 and 2) acts as a genetic switch that initiates gene expression through interactions with c-rel (15,16) and atypical NF-κB inhibitor (17). Accordingly, targeting CNS3 chromatin accessibility with a specific ribonucleoprotein (dCas9-catalytically inactive variant of clustered regularly interspaced short palindromic repeats-associated protein 9) has been shown to promote FOXP3 expression in Jurkat cells (18), whereas endogenous long non-coding RNA (FLICR-Foxp3 long intergenic non-coding RNA) induces a FOXP3 low T-cell subset (19). Although high FOXP3 expression levels are commonly attributed to CD4 + CD25 high Treg cells, FOXP3 is also induced by TCR stimulation in naive CD4 + CD25 − T cells and persists for several days in activated CD4 + T cells (20).…”
Section: Ipex Mutations Target Foxp3-the Indispensable Immune Regulatormentioning
confidence: 99%
“…CNS3 located at FOXP3 intron 1 (i.e., between exon 1 and 2) acts as a genetic switch that initiates gene expression through interactions with c-rel (15,16) and atypical NF-κB inhibitor (17). Accordingly, targeting CNS3 chromatin accessibility with a specific ribonucleoprotein (dCas9-catalytically inactive variant of clustered regularly interspaced short palindromic repeats-associated protein 9) has been shown to promote FOXP3 expression in Jurkat cells (18), whereas endogenous long non-coding RNA (FLICR-Foxp3 long intergenic non-coding RNA) induces a FOXP3 low T-cell subset (19). Although high FOXP3 expression levels are commonly attributed to CD4 + CD25 high Treg cells, FOXP3 is also induced by TCR stimulation in naive CD4 + CD25 − T cells and persists for several days in activated CD4 + T cells (20).…”
Section: Ipex Mutations Target Foxp3-the Indispensable Immune Regulatormentioning
confidence: 99%
“…Overexpression of the transcription factor HELIOS cooperates with FOXP3 to generate both CD4 + and CD8 + Treg from human Tconv, but particularly CD8 + T cells ( 20 ). Similarly, delivery of dCas9 fused to a transcriptional activator and guides recognizing FOXP3 promoter sequences increases FOXP3 expression ( 104 ).…”
Section: Genetic Engineering Strategies For Enhanced Stability and Fumentioning
confidence: 99%
“…Although not applied in pre-clinical studies, a number of early works also suggest that dCas9-based methods can help circumvent other major tumor immunoevasion mechanisms. For instance, impairment of Treg immunosuppressive function by dCas9-KRAB-mediated forkhead box P3 (FoxP3) transcriptional repression, 139 , 140 dCas9-SAM-mediated enhancement of neoplastic transformation markers, such as MICA, 141 , 142 and dCas9-KRAB-directed repression of immunosuppressive cytokine receptors 143 have demonstrated that dCas9-mediated epigenetic engineering has potential in multiple facets of cancer immunotherapy. Ultimately, dCas9-mediated epigenetic editing to improve tumor immunogenicity and/or boost the host’s anti-tumor immune response opens new therapeutic avenues, particularly in combination with ICI or ACT therapies ( Figure 2 ).…”
Section: Epigenetic Editing By Crispr-dcas9 Can Improve Anti-tumor Host Immunitymentioning
confidence: 99%